Grey matters - Peralejo, Maria Francesca C.; Abaya, Leo Antonio (Quezon City College of Fine Arts, University of the Philippines Diliman, 2010)
Everyday we are flooded with sensory input, which must quickly be organized into manageable categegories, from the interactions we make. Stereotyping evolves from this simple need for classification. Stereotypes may root from more or less accurate critical thinking becomes limited. Furthermore, stereotyping affects people - we unconsciously mold ourselves to live up the standards of the stereotypes that society perpetuate which causes us to harm and limit ourselves. However, we can free ourselves from the confines of these boxes once we refer to them as impractical ideals. Ultimately, be desirable, but it isn't as important as self acceptance. Physical appearance, being a critical aspect of stereotyping (Lips, 2005), is where gender stereotyping usually materializes. Given that, I used photography as an art form to critique the stereotypes it establishes. My attempt to critique our long-held opinions of ourselves and the others, searches for ways to view life and to portray it; communicates my ideas and opinions; and tries to make people aware of these things. I utilized nonconforming attributes of a sexed person with gendered individuals, which I observed, assembled a tableau of objects and figures, and shot those scenes to ambiguate the representation of gender in photographs. The photos were preconceived. Choosing and eliminating elements - selecting the suitable models and proper venues, cropping, disregarding color, etc - in my works were made to force a concentration to the form created by it. I reckon photography to reveal the origins and manifestation of the subjects' expressions. being a visual art, I believe that it is capable of depicting matters such as this. photographs allow what they show to be appropriated by reflection (Berger, 1982). Photographs really are experiences captured, and the camera is t ideal arm of consciousness in its acquisitive mood (Sontag, 1990).
Thesis (Bachelor of Fine Arts in Studio Arts) - -University of the Philippines Diliman
Bibliography : leaf 23.
Keywords: Photography; Gender identity in art